2009
DOI: 10.1111/j.1743-6109.2009.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Workload on Seat Pressure While Cycling with Two Different Saddles

Abstract: Introduction Seat pressure during cycling and its relationship to urological disorders have been discussed extensively in recently published literature. The effects of exercise configuration on seat pressure, however, still have not been fully investigated. Aim This study evaluates the effects of two different pedaling workloads and two saddle designs on saddle pressure in 22 (11 men and 11 women) recreational cyclists (bicyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…31,32 Concerning the role of a perineal hole, it has been shown that a central cut-out did not lessen perineal pressure but, on the contrary, could increase it. 16,[33][34][35] Sommer et al 32 attributes this to the fact that the positioning of the hole might not be well understood by manufacturers. Indeed, improper placement of the cut-out Saddle size (wide 5 narrow) A wide enough saddle that supports the ischial tuberosities results in less perineal compression Saddle geometry (nose 5 partial cut-out 5 complete cut-out)…”
Section: Bicycle Characteristicsmentioning
confidence: 98%
“…31,32 Concerning the role of a perineal hole, it has been shown that a central cut-out did not lessen perineal pressure but, on the contrary, could increase it. 16,[33][34][35] Sommer et al 32 attributes this to the fact that the positioning of the hole might not be well understood by manufacturers. Indeed, improper placement of the cut-out Saddle size (wide 5 narrow) A wide enough saddle that supports the ischial tuberosities results in less perineal compression Saddle geometry (nose 5 partial cut-out 5 complete cut-out)…”
Section: Bicycle Characteristicsmentioning
confidence: 98%
“…This was true of riders using both traditional and cut-out saddles; however, a direct comparison between those riding traditional vs. cut-out saddles was not reported. In a subsequent study, the authors compared the saddle pressures of the women using cut-out saddles with those using a gel cushioned, solid-nosed saddles and found that at a fixed workload of 150 W, peak total saddle pressures were significantly increased when riding on a cut-out saddle compared with a traditional saddle [15].…”
Section: Discussionmentioning
confidence: 99%
“…Using a central cutout saddle resulted in a non-significant increase in total, a significant decrease in anterior, and a significant increase in posterior seat pressures compared with a standard saddle [25,41]. An observational study by Dettori et al [7] has shown that using cutout saddle is associated with a slightly greater risk of erectile dysfunction among cyclists with perineal numbness.…”
Section: Different Types Of Saddlementioning
confidence: 99%
“…This approach omits several important conditions associated with cycling in the field setting. The notable examples include different terrain, oscillations, and varying workloads, which could affect the perineal pressure and comfort of the bicycle user [38,41]. Additionally, most of the included studies consisted of just a few, relatively short sessions.…”
Section: Practical Implications and Limitationsmentioning
confidence: 99%